2015
DOI: 10.1590/s0100-83582015000400010
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping Corn With a Combination of Tree Species to Control Weeds

Abstract: -The combination of crop residues or crop extracts is often more advantageous in controlling weeds, than the application of each residue or extract singly. This suggests that in intercropping with maize, the combination of tree species can be more advantageous than species isolated in weed control. The objective of this study was to evaluate the effects of intercropping with a combination of leguminous on the weed growth and corn yield. A randomized-block design with split plots (cultivars in plots) and five r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…The average values of height (84.83 cm) and width (87.64 cm) of cacti obtained from this research are similar to the values reported by da Silva et al (2015) for the genotypes Miúda (68.11 cm height and 88.44 cm width) and Orelha de Elefante Mexicana (80.56 cm height and 101.78 cm width) evaluated at 2 yr after planting in dry conditions in the municipality of Serra Talhada, Pernambuco, Brazilian semi-arid region.…”
Section: Agronomic Yieldsupporting
confidence: 89%
See 2 more Smart Citations
“…The average values of height (84.83 cm) and width (87.64 cm) of cacti obtained from this research are similar to the values reported by da Silva et al (2015) for the genotypes Miúda (68.11 cm height and 88.44 cm width) and Orelha de Elefante Mexicana (80.56 cm height and 101.78 cm width) evaluated at 2 yr after planting in dry conditions in the municipality of Serra Talhada, Pernambuco, Brazilian semi-arid region.…”
Section: Agronomic Yieldsupporting
confidence: 89%
“…Forage cactus is widely cultivated in the Brazilian semi‐arid region and is mainly used for animal feed in times of rainfall scarcity (Aguiar et al., 2019). Intercropping (companion cropping) of two or more plant species is a sustainable agricultural approach that can result in numerous environmental and economic benefits such as improved functioning of soil microbial communities, recovery of soil fertility, and consequent increase in production (Curtright & Tiemann, 2021; Raza et al., 2021; P. Silva et al., 2015). In fact, intercropping can reduce water demand and improve water use efficiency, thus reducing water consumption in agriculture (Raza et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabela 1 -Altura (cm) de mudas de Gliricidia sepium, submetidas à competição com plantas daninhas ao longo de 60 dias após transplantio (DAT) Estudos apontam a capacidade supressora da cobertura morta de ramos de gliricídia sobre as plantas daninhas ou sua contribuição no controle das infestantes quando em consorciação com o milho (Oke, 2012;Fernades;Chicas, 2015;Oliveira, 2020). Contudo, no presente estudo verificouse a suscetibilidade das mudas da espécie arbórea à interferência causada pelas plantas daninhas.…”
Section: Resultados E Discussõesunclassified
“…In this study, although intercropping of baby corn with pulse legumes did not significantly reduce baby corn growth and productivity, they did reduce growth and productivity of the corn in all treatment combinations and the most reductions were found in baby corn with crawling cowpea and mungbean, respectively. The reductions in growth and productivity of baby corn were not surprising as pulse legumes acted as weeds that competed with baby corn for water, nutrients and solar radiation (Silva et al, 2015). As nitrogen fixing crops and pulse legumes, the authors expected to find the benefit of the legumes from nitrogen fixation and the additional income that was high enough to reimburse the crop loss from competition.…”
Section: Crop Productivitymentioning
confidence: 99%